Recent Advances in Forensic Medicine: An Overview - Panga, Surya Kiran; Balaji D; Dubey, Harshita; Dwivedi, Shivam; Yadav, Abhishek; Rathod, Gunvanti B.; Singh, Gyanendra; Ranjan, Amar; Anupurba, Shilpa; Sharma, Anil; Anandani, Garima; Mittal, Gyanendra S (Medical Science: Recent Advances and Applications Vol. 3, 2025)
Forensic medicine has undergone transformative advancements, integrating cutting-edge technologies that significantly enhance the precision, efficiency, and scope of medico-legal investigations. Innovations such as Virtopsy, robotic systems, and AI-based technologies have redefined postmortem analysis and crime scene reconstruction, enhancing precision and minimising human bias. Rapid and mobile DNA platforms provide immediate identification benefits in time-sensitive contexts such as mass disasters and border security. AI-driven algorithms further augment DNA mixture interpretation, phenotype prediction, and automated evidence evaluation. Despite these advancements, it is imperative to ensure rigorous validation, standardisation, and ethical scrutiny to maintain evidentiary reliability within judicial systems. In this article, these recent innovations, emphasising their impact on forensic investigations and the need for robust validation, were explored to ensure their admissibility in legal proceedings. Forensic medicine has undergone transformative advancements, integrating cutting-edge technologies that significantly enhance the precision, efficiency, and scope of medico-legal investigations. Innovations such as Virtopsy, robotic systems, and AI-based technologies have redefined postmortem analysis and crime scene reconstruction, enhancing precision and minimising human bias. Rapid and mobile DNA platforms provide immediate identification benefits in time-sensitive contexts like mass disasters and border security. AI-driven algorithms further augment DNA mixture interpretation, phenotype prediction, and automated evidence evaluation. Despite these advancements, it is imperative to ensure rigorous validation, standardisation, and ethical scrutiny to maintain evidentiary reliability within judicial systems. In this article, we explore these recent innovations, highlighting their impact on forensic investigations and emphasising the need for robust validation to ensure their admissibility in legal proceedings.